Hubungan Faktor Individu terhadap Stress Kerja pada Karyawan Operasi PT-XYZ Tahun 2023 - Wicaksono, Faridl; Susilowati, Indri Hapsari; Susanto, Arif (Jurnal Kesehatan Komunitas, 2024)
There were 19.67 injuries per 200,000 hours worked by mining employees in 2019 in Ghana, the injuries were due to the gap between mining operations and the knowledge and skills of their workers. These gaps can generally lead to work stresss. Various factors can cause work stresss, both caused by individual factors and work-related factors. This study aims to analyze these factors on work stresss in mining operation employees PT-XYZ. The research respondents amounted to 226, divided into 5 departments, namely Construction, Processing, Geotechnical, Underground mining operations (Ops.) and Repair operations (Mtc.). This quantitative research design uses cross-sectional study research methods. The dependent variable in the form of work stress was measured using the Depression, Anxiety and Stress Scale-21 (DASS-21) while the independent variables in the form of age, education, length of work, gender, and worker status were taken using general questionnaire. The data analysis technique in this study used the Chi-square test. There were 46 respondents (20.4%) experiencing work stress. This study showed a significant relationship between the age factor of workers (0.03) and gender (0.05) of workers with work stress in employees of PT-XYZ mining operations. Understanding the age and sex factors of workers that affect work stress can provide an overview for PT-XYZ to formulate policies, appropriate procedures, and interventions in managing mining safety.